Thyroid Dysfunction and Cytological Patterns among Patients Requested for Thyroid Function Test in an Endemic Goiter Area of Gondar, North West Ethiopia - Daniel Asmelash; Kumlgn Tesfa; Belete Biadgo (International Journal of Endocrinology)
Background. Thyroid dysfunction is the most common endocrine disorder in clinical practice, and about half of the population with thyroid dysfunction remains undiagnosed. There is a fairly wide spectrum of thyroid dysfunction, which can be identified by patterns of thyroid function test results. The prevalence of thyroid dysfunction among the population varies in different studies. Methods. A cross-sectional study was conducted from February 8th to April 8th, 2017, among patients who requested for the thyroid function test in an endemic goiter area at the Gondar Hospital, University of Gondar. A pretested structured questionnaire was used to collect the data. Three milliliters of blood samples was collected in a plain test tube and centrifuged for serum separation. The thyroid function test was done by using the MINI-VIDAS automation following the manufacturer manual (Setema PLC, Italy). Data were entered and analyzed using SPSS version 20. Descriptive statistics were used for data presentation, and P value < 0.05 was considered significant. Result. Of the total 384 study participants, 346 (90.1%) were females and the study participants’ mean age was 38 ± 13.9 years. The overall thyroid dysfunction prevalence was 26.3% (101): 1.6% was identified as subclinical hypothyroidism, 0.5% hypothyroidism, 9.6% subclinical hyperthyroidism, and 14.6% hyperthyroidism, and 23.4% had goiter. Furthermore, for cytological pattern analysis, 144 study participants who fulfilled indications for fine-needle aspiration cytology (FNAC) in thyroid nodules were included. Of the total, 3 (2.1%) had thyroid carcinoma, 46 (32%) had cystic degenerated follicular cells, and 82 (57%) had nodular thyroid goiter. In addition, a clinical presentation of a total of 144 study participants, showed lymphadenites in 7 participants (4.8%), hypertension in 9 (6.2%), and cardiac failure in 12 (8.3%). Conclusion. The prevalence of thyroid dysfunction was high. The majority of thyroid dysfunction cases were newly diagnosed and more common in females. In addition, the most common disorders were subclinical hyperthyroidism and hyperthyroidism. Follicular cell with cyst degeneration and thyroid nodular goiter were the predominant FNAC findings. For early diagnosis and appropriate intervention in goiter endemic areas, the thyroid function test should be closely monitored.